Rethinking Community-Based Waste Governance in Informal Urban Settlements - Rajagukguk, Jenni Ria (Universitas Syiah Kuala, 2025)
Waste management in informal settlement areas in Indonesia is still a complex environmental issue. Limited government services, population density, and minimal infrastructure conditions make waste a major source of pollution and health risks. In the last ten years, the community-based waste governance (CBWG) approach has been widely encouraged by local governments and civil society organizations. However, the effectiveness of this approach varies, depending on local capacity, policy support, and sustainability of citizen participation. This study aims to review the CBWG approach in Indonesia's informal settlements by examining the factors that strengthen or weaken the initiative. The study was conducted in three major cities through a qualitative method that included in-depth interviews with residents, community leaders, NGOs, and environmental officials, as well as participatory observation at the RT/RW level. The results showed that the success of the CBWG was greatly influenced by strong community leadership, economic incentives from recycling activities, and synergy between residents and local government support. On the contrary, fragmentation of responsibilities and lack of long-term planning are the main obstacles. These findings emphasize the importance of building a hybrid governance model that combines local wisdom, institutional support, and social innovation to realize an inclusive, sustainable, and contextual waste management system for informal areas in Indonesia.